Using Transmissibility And Vibration Power Flow Methods To Evaluate The Effectiveness Of Elastomeric Mounts For Vibration And Noise Control - Azma , Putra; Md Rejab, Mohd Noor Arib; Abd Rahman, Roslan; Raja Hamzah, Raja Ishak; Jawaid Iqbal, Inayat-Hussain; Ahmad , Nazirah; Ismail , Asyraf (International Institute of Acoustics and Vibration, 2014)
This paper presents the results of an experimental evaluation of elastomeric mounts used to isolate vibration from a block (representing a powertrain) to a structure test rig (representing a vehicle structure). Four types of elastomeric mounts were considered, where three of them are from green material natural rubber (SMR CV60, ENR50 and DPNR) and one from petroleum based synthetic rubber (EPDM). Measurement of the dynamic stiffness and loss factor of these elastomers were initially performed. Dynamic stiffness and loss factor were measured in the axial direction for a range of frequency between 5 Hz and 150 Hz at with a dynamic amplitude of 0.2 mm (p-p). Shaker excitation using random vibration signal in the frequency range of 10 Hz to 150 Hz at constant force magnitude was applied to the block in order to quantity the effectiveness of the elastomeric mounts. Measured vibration amplitudes in the axial direction on both sides of each mount were used to calculate the transmissibility and vibration power flow. Sound radiation from a plate attached to the structure test rig was also measured to evaluate the elastomeric mounts contribution to structure-borne noise. The results from transmissibility showed that vibration was high on EPDM, particularly in the ranges 25 to 35 Hz, 60 to 80 Hz and 100 to 120 Hz. ENR50 ability to reduce or damped the amplitude at resonance was found to be the best as compared to the other elastomers. The to- tal vibration power flow was observed to be highest on ENR50 followed by EPDM. The high transmissibility on EPDM was due to its high dynamic stiffness and low loss factor. The larger total vibration power flow on ENR50 was attributed to its high dynamic stiffness and high loss factor.